Mathematic simulation of transient process in a.c. – system “Electric traction network – Locomotive” 1. Switch on locomotive’s power converter in “free play” mode; parameters estimation - Mishchenko, T. M.; Kiiko, A. I. (Science and Transport Progress, 2011)
In the article the electric circuit of substitution and mathematical model of the system of alternating current «traction substation − traction mains − electric locomotive DS 3» at switching its power transformer on in the idle mode are presented. Numerical determinations of parameters of traction substation, rails, contact network and transformer are executed; in so doing a special attention is paid to the estimation of dispersion inductance for the primary winding of transformer.